Sputum Neutrophilia Can Mask Eosinophilic Bronchitis During Exacerbations - Liesel D’silva; Christopher J Allen; Frederick E Hargreave; Krishnan Parameswaran (Canadian Respiratory Journal)
BACKGROUND: Exacerbations of airway disease are eosinophilic, neutrophilic, both or neither. The primary objective of the present study was to identify whether the treatment of a neutrophilic bronchitis can unmask an associated eosinophilia.